Heavily and fully modified RNAs guide efficient SpyCas9-mediated genome editing - Aamir Mir (Nature Portfolio, 2018)
Resistance of gRNA to ubiquitous ribonucleases is required for CRISPR-Cas9-based therapeutics. Here, the authors explore chemical modifications at all positions of the crRNA guide and tracrRNA cofactor, and identify modified versions that are more potent and stable than their unmodified counterparts in editing human cells.